PROGRAM PENGEMBANGAN BUDAYA KEWIRAUSAHAAN BAGI MAHASISWA PERGURUAN TINGGI MELALUI KETERAMPILAN PERCETAKAN - Rubiyanto, Rubino (Universitas Muhammadiyah Surakarta, 2007)
Untill predominate out-comes of the CollegeÂ are job seeker.Â TochangeÂ the mind setÂ them to become the job creator presumably need aneffort, stock purchasing andÂ giving of capital entrepreneur. Therefore noits bad if the student FKIP to made as a professional teacher candidate,also given entrepreneur lecturer.Â This lecturer is programmed in anpackage: KWU in the field of offset printing skill. Target of this activity is:(a) develop the culture of entrepreneur in PT, (b) the student have thestock of science and skill of offset printing area, (c) student have theknowledgeÂ about trick of the trade, developing idea of effort, managingeffort, marketing strategy and obtain;get the capital employed, (d)student have the readiness of business. The target of this activity are 30studentâs of FKIP in semester VI from various program. Lecturing methodcover the discourse, discussion, duty, question and answer, compilationof proposal business, seminar proposal, simulation and also practice inprinting office. Resistance met by execution KWU at the same time bylecturer fundamental so that execution entrepreneur delayed. Finally theenterpreur program areÂ executedÂ after even semester test 2006 finishing.Activity exterior for example; 1) piled up over by module entrepreneur,vision of business mission, career tuition, credit system of this effort; 2)piled up over by proposal business in group; 3) the expectedÂ after studentpass, 25 % participant earn the entrepreneur offset printing.